Nucleic Acid Testing for Coronavirus Disease 2019: Demand, Research Progression, and Perspective. (2nd March 2022) - Zhang, Shiyin; Su, Xiaosong; Wang, Jin; Chen, Mengyuan; Li, Caiyu; Li, Tingdong; Ge, Shengxiang; Xia, Ningshao
Abstract: The current coronavirus disease 2019 (COVID-19) outbreak, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a public health emergency of international concern. There has been a surge in demand for COVID-19 diagnostic reagents, as timely detection of virus carriers is one of the most important components of disease prevention and control. Nucleic acid testing (NAT), with high sensitivity and specificity, is considered the "gold standard" for the diagnosis of COVID-19. Therefore, more than 700 research units and companies have been devoted to developing NAT reagents. To date, nearly 600 research units and companies have claimed to have completed the development of NAT reagents. The use of these products has a positive effect on disease prevention and control; however, exaggerated claims and inadequate understanding of the products have led to improper access to reagents and equipment in clinics. This has resulted in chaos in the clinical diagnosis of COVID-19. Herein, we have overviewed the COVID-19 NAT products, including their principles, corresponding advantages and disadvantages, relevant circumstances for application, and respective roles in epidemic containment. Our comments may provide some references for assay developers and aid clinical staff in choosing the appropriate class of test from the different tests available.